2nd International Ankle Symposium 2004 Newark (2004)
Abstracts of the reports held at the 2nd International Ankle Symposium 2004 Delahunt, E.: Preliminary results from an Investigation into the nature of movement dysfunction during running in individuals with functional ankle instability (FAI) De Noronha: Landing from a jump: Pilot of a new jump test Tillman, M.D.: Detection of dynamic stability deficits in subjects with functional ankle instability Monaghan, K.: Preliminary results from a 3D motion analysis investigation of the kinematic and kinetic patterns associated with mechanical instability (MI) and functional instability (FI) of the ankle compared to normals during gait Worrell, T. W.: Talar bone spur, ligament damage, and severe synovitis following inversion sprain: A case report Hyer, C. F.: Thermal capsular modification in the functionally unstable ankle Yamamoto, H.: Anatomical reconstruction of the lateral ankle ligaments using gracilis tendon fixed with endobuttons Spitalny, A. D.: Retrospective review of 500 brostroms: Necessity of ankle arthroscopy Manal, K.: Developing and testing an EMG-driven model to estimate ankle moments and muscle forces during walking Arnold, B. L.: Low-load force sense deficits are related to frequency of ankle giving-way Gribble, P. A.: Chronic ankle instability and fatigue create proximal joint alterations during performance of the star excursion balance test Kaminski, T. W.: Examining Functional Strength Ratios between Those with Ankle Instability and a Control Group with Uninjured Ankles Freccero, D. M.: The Relationship between Tears of the Peroneus Brevis Tendon and Distal Extent of Its Muscle Belly Saldanha, V.: Measurement of Lateral Ligament Length under Load Using 3D Stress MRI Kovaleski, J. E.: The Effect of Load Range and Lateral Ligament Sectioning on Stiffness and Laxity of the Ankle-Subtalar Joint Complex Bischof, G.: Biomechanical Gait Analysis of Ankle Instability in Extremely Obese People Vicenzino, B.: Mobilization of Movement Treatment of the Ankle Changes Joint Position Sense in Subjects with Recurrent Sprains: A Preliminary Report Eechaute, C.: Effects of a Six Week Wobble Board Training Program on a Sudden Inversion in the Standing Position in Patients with Functional Ankle Instability Gustavsen, G. P.: A Single Electrical Stimulation of the Peroneal Nerve Improves Symptoms Seen in Chronic Functional Ankle Instability and Impacts Dorsiflexor/Plantar Flexor Reciprocal Muscle Group Ratios Hale, S. A.: Efficacy of a Four-Week Rehabilitation Program in Managing Chronic Ankle Instability Berschin, G.: Muscle Fatigue, Imbalance of Muscle Activity, and Ankle Joint Trauma Brown, C. N.: Comparing Ankle Joint Ability of Individuals with Unilateral and Bilateral Chronic Ankle Instability Using the Ankle Assessment Questionnaire Docherty, C. L.: Postural Control Deficits in Participants with Functional Ankle Instability as Measured by the Balance Error Scoring System Gustavsen, G. P.: A Single Peroneal Nerve Stimulation Improves Neuromuscular Deficits in Chronic Functional Ankle Instability Hiller, C. E.: Development and Testing of a Tool for Measuring Functional Ankle Instability Hubbard, T. J.: Anterior Fibular Position in those with Self-reported Unilateral and Bilateral Chronic Ankle Instability Kumar, M.: Effect of Mild Motion on Ankle Stiffness in Diabetic Patients Liu, X.: 3D Characterization and Localization of Anatomical Landmarks of the Foot by Fastscan Mattacola, C.G.: Muscular Contributions of the Anterior and Posterior Tibialis, Gastrocnemius, and Fibularis Longus with and without Orthotics during Bilateral Stance Mclachlan, K.: The Inter-Day Reliability of Ankle Musculotendinous Stiffness Measures Nilsson, G. Postural Stability in Ankle Fractures: 14-Month Follow-Up Olmsted-Kramer, L. C.: Is There a Link between Ankle Sprain History and Anterior Cruciate Ligament Injury Risk? Ross, S. E.: Effect of Coordination Training with and without Exercise Sandals on Static Postural Stability of Individuals with Functional Ankle Instability and Individuals with Stable Ankles Spitalny, A. D.: Retrospective Review of 300 Ankle MRIs and 500 Brostroms: Peroneal Tendon Pathology (1) (2) Wikstrom, E. A.: Reliability and Validity of a New Measure of Dynamic Stability: The Dynamic Stability Index